2017
DOI: 10.1039/c7cy00710h
|View full text |Cite
|
Sign up to set email alerts
|

Oxide-based nanomaterials for fuel cell catalysis: the interplay between supported single Pt atoms and particles

Abstract: The concept of single atom catalysis offers maximum noble metal efficiency for the development of lowcost catalytic materials. Among possible applications are catalytic materials for proton exchange membrane fuel cells. In the present review, recent efforts towards the fabrication of single atom catalysts on nanostructured ceria and their reactivity are discussed in the prospect of their employment as anode catalysts.The remarkable performance and the durability of the ceria-based anode catalysts with ultra-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
89
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 159 publications
1
89
0
2
Order By: Relevance
“…Pt−O−Ce bond was observed at 71.9 eV clarified by Mori et al ., which was also similar to the reported Ru‐O−Ce bond . Pt−O−Ce bonds in C/PBI/Pt@CeO x were supposed to be formed during the hydrothermal process, agreeing well with previous report . The partially ionized Pt was beneficial for boosting the stability of Pt electrocatalyst since partial ionization made Pt nanoparticles difficult to coalesce/aggregate .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Pt−O−Ce bond was observed at 71.9 eV clarified by Mori et al ., which was also similar to the reported Ru‐O−Ce bond . Pt−O−Ce bonds in C/PBI/Pt@CeO x were supposed to be formed during the hydrothermal process, agreeing well with previous report . The partially ionized Pt was beneficial for boosting the stability of Pt electrocatalyst since partial ionization made Pt nanoparticles difficult to coalesce/aggregate .…”
Section: Resultssupporting
confidence: 90%
“…[19] PtÀOÀCe bonds in C/PBI/ Pt@CeO x were supposed to be formed during the hydrothermal process, agreeing well with previous report. [14] The partially ionized Pt was beneficial for boosting the stability of Pt electrocatalyst since partial ionization made Pt nanoparticles difficult to coalesce/aggregate. [16] It's worth noting that increment in Ce(III) content indicated that more Pt atoms were ionized at the interfaces and higher oxygen vacancy of CeO x was obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly dispersed platinum nanoparticles (NPs) deposited on oxide supports are commonly used as the active components of catalysts for practically important processes, such as neutralization of harmful gases in automobile converters, reactions in fuel cells, preferential oxidation of carbon monoxide (PROX) reaction, and CO oxidation …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although the Pt 2+ was found to be thermally and chemically stable, it is apparently inactive for the dissociation of H 2 17 , and thus ineffective for hydrogenation reactions. A full review of the findings was recently published 18 , but in general, the authors conclude that Pt 2+ cations do not interact strongly with adsorbates, and that subnano Pt nanoparticles are likely responsible for catalytic activity arising in this system. 2+ clearly dominates, and is very stable, when the ceria support has a high step density.…”
mentioning
confidence: 99%